2015
DOI: 10.5194/amt-8-2001-2015
|View full text |Cite
|
Sign up to set email alerts
|

Comparing satellite- to ground-based automated and manual cloud coverage observations – a case study

Abstract: Abstract. In this case study we compare cloud fractional cover measured by radiometers on polar satellites (AVHRR) and on one geostationary satellite (SEVIRI) to ground-based manual (SYNOP) and automated observations by a cloud camera (Hemispherical Sky Imager, HSI). These observations took place in Hannover, Germany, and in Lauder, New Zealand, over time frames of 3 and 2 months, respectively.Daily mean comparisons between satellite derivations and the ground-based HSI found the deviation to be 6 ± 14 % for A… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
19
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 42 publications
5
19
0
7
Order By: Relevance
“…A similar observation was cited in [Román et al, 2017a, ]. In [Werkmeister et al, 2015, ] the observations took place in Germany and New Zealand, over time frames of 3 and 2 months, respectively. For a clear sky, the authors found detection probabilities of between 72 and 76%.…”
supporting
confidence: 72%
See 1 more Smart Citation
“…A similar observation was cited in [Román et al, 2017a, ]. In [Werkmeister et al, 2015, ] the observations took place in Germany and New Zealand, over time frames of 3 and 2 months, respectively. For a clear sky, the authors found detection probabilities of between 72 and 76%.…”
supporting
confidence: 72%
“…In addition, sky cameras have been used to record cloud detection from solar radiation data [Alonso et al, 2014a, ] and then to predict 45 the solar resource over the short term using digital levels and maximum cross-correlation [Alonso-Montesinos and Batlles, 2015; Alonso-Montesinos et al, 2015, ]. Other authors have compared cloud detection data using satellite imagery and sky cameras [Luiz et al, 2018;Werkmeister et al, 2015, ];in [Luiz et al, 2018, ], the comparison was made in south-eastern Brazil over a period of approximately three months. Good agreement was obtained for clear sky and overcast conditions, with detection probabilities of 92.8% and 80.7%, respectively.…”
mentioning
confidence: 99%
“…However, the temporal resolution of satellite products is limited. From the Meteosat Second Generation (MSG) geostationary satellites, for instance, data on clouds are taken with a time resolution of 15 min (Werkmeister et al, 2015). Therefore, and for the validation of cloud products from satellites, ground-based observing systems such as all-sky cameras are necessary.…”
Section: Introductionmentioning
confidence: 99%
“…An alternative to detecting clouds from the ground by human observation is to detect them from space. With a temporal resolution of 5 to 15 min, Meteosat Second Generation (MSG) geostationary satellites are able to detect cloud coverage with a higher time resolution than is accomplished by human observers (Ricciardelli et al, 2010;Werkmeister et al, 2015). The geostationary satellite Himawari-8 (Da, 2015) even delivers cloud information with a temporal resolution of 2.5 to 10 min and a spatial resolution of 0.5 to 2 km.…”
Section: Introductionmentioning
confidence: 99%